Analysis and Construction of a Competitive Endogenous RNA Regulatory Network of Baicalin-Induced Apoptosis in Human Osteosarcoma Cells - Lan, Haifeng (Biomed Res Int, 2021)
BACKGROUND: Baicalin is an extract from the traditional Chinese herb Scutellaria baicalensis and has the potential to treat osteosarcoma (OS). However, the transcriptome-level mechanism of baicalin-mediated antitumor effects in OS has not yet been investigated. The aim of this study was to analyze the competitive endogenous RNA (ceRNA) regulatory network involved in baicalin-induced apoptosis of OS cells. METHODS: In this study, CCK-8 and flow cytometry assays were used to detect the antitumor effects of baicalin on human OS MG63 cells. Furthermore, transcriptome sequencing was employed to establish the long noncoding RNA (lncRNA), microRNA (miRNA), and mRNA profiles. RESULTS: Baicalin inhibited MG63 cell proliferation and induced apoptosis. Totals of 58 lncRNAs, 31 miRNAs, and 2136 mRNAs in the baicalin-treated MG63 cells were identified as differentially expressed RNAs compared to those in control cells. Of these, 2 lncRNAs, 3 miRNAs, and 18 mRNAs were included in the ceRNA regulatory network. The differentially expressed RNAs were confirmed by quantitative real-time PCR (qRT-PCR). CONCLUSIONS: By identifying the ceRNA network, our results provide new information about the possible molecular basis of baicalin, which has potential applications in OS treatment.